2017
DOI: 10.1002/iub.1701
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of yeast and fungal Na+/H+ antiporters

Abstract: Sodium proton antiporters (or sodium proton exchangers [NHEs]) are a critical family of membrane proteins that exchange sodium for protons across cell membranes. In yeast and plants, their primary function is to keep the sodium concentration low inside the cytoplasm. One class of NHE constitutively expressed in yeast is the plasma membrane Na 1 /H 1 antiporter, and another class is expressed on the endosomal/ vacuolar membrane. At present, four bacterial plasma membrane antiporter structures are known and nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 85 publications
(158 reference statements)
1
31
0
Order By: Relevance
“…3 ). Consistent with our findings, these eight positions were recently proposed to be important for the function and regulation of eukaryotic and archaeal CPA1s, based on a few representatives 38 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…3 ). Consistent with our findings, these eight positions were recently proposed to be important for the function and regulation of eukaryotic and archaeal CPA1s, based on a few representatives 38 .…”
Section: Resultssupporting
confidence: 91%
“…3b , see also ref. 38 ), while in CPA2s it can feature any residue. Therefore, we refer to it as E 5 when discussing CPA1s and - 5 in the context of CPA2s.…”
Section: Resultsmentioning
confidence: 99%
“…The function of some of them has also been elucidated by the deletion of the corresponding gene and characterization of phenotypes of resulting mutants (e.g., Schizosaccharomyces pombe , C. albicans , and C. glabrata ; reviewed in Ramos et al, ). S. cerevisiae Nha1 and S. pombe Sod2 (recently renamed to SpNHE1; Dutta & Fliegel, ) are among the first yeast alkali metal cation antiporters to be isolated and characterized, together with those of Zygosaccharomyces rouxii and C. albicans , and are the two best studied yeast antiporters (Ariño et al, ). In fact, SpSod2 was the first yeast transport system with a Na + /H + antiport mechanism characterized.…”
Section: The Nha Efflux Systemmentioning
confidence: 99%
“…The detailed structure of a yeast NHA antiporter has not been elucidated yet, and some predictions have been made using the known crystal structure of several bacterial homologues (e.g., Escherichia coli NhaA; Hunte et al, ). Numerous studies revealed the importance of various amino acid residues, mainly charged or polar ones located in the transmembrane segments, on the antiporter activity and substrate specificity (e.g., Dibrov, Young, & Fliegel, ; Kinclova‐Zimmermannova, Zavrel, & Sychrova, , ; reviewed recently in Dutta & Fliegel, ). Several of these amino acid residues seem to be conserved in the Na + /H + antiporters of all organisms and are proposed to be directly involved in the translocation of ions and protons through the antiporter.…”
Section: The Nha Efflux Systemmentioning
confidence: 99%
See 1 more Smart Citation